PREVALÊNCIA DO VÍRUS ZIKA EM DOADORES DE SANGUE DE UM SERVIÇO DE HEMOTERAPIA DA REGIÃO SUL DO BRASIL - Diefenbach, Cristiane Fração (2017)
The Zika Virus (ZIKV) is a flavivirus, which is responsible for causing an emerging arbovirosis in Brazil what is primarily transmitted by the bite of infected mosquitoes of the genus Aedes. A much discussed transmission route lately is blood transfusion due to the large number of asymptomatic cases and the epidemic potential of ZIKV that causes epidemics of great proportions. As such, asymptomatic individuals may contaminate blood components and thereby participate in the transfusion transmission of this infection. The disease has a benign clinical picture but serious clinical consequences have been reported, such as Guillain-Barré syndrome (GBS) and fetal malformations such as microcephaly. Due to this fact, recently, the Health Ministry (HM) declared the infection by ZIKV a Public Health Emergency of National Importance (PHENI). Thus, the major challenge for blood banks is the transfusion prevention of ZIKV due to lack of licensed laboratory routine tests for blood donor screening. In the South region of Brazil there is no epidemiological study in this population. This study will allow a robust assessment of the current epidemiological situation in this region. The objective of the study is to estimate the seroprevalence and asymptomatic viremia of ZIKV in blood donors of a Hemotherapy Service in the southern region of Brazil. In this study, blood samples were collected from 500 donors in the period from December 2016 to January 2017. The biological materials were tested for the presence of ribonucleic acid (RNA) from ZIKV, by means of real-time reverse transcription polymerase chain reaction (RT-PCR) test by commercial kit (TaqPath™ Zika Virus Kit (ZIKV) and enzyme-linked immunosorbent assay (ELISA) serologically assessed for anti-ZIKV IgG using Anti-Zika Virus ELISA IgG kit (Euroimmun, Medizinische Labordiagnostika AG, Lübek, Germany). No samples showed positive results for ZIKV RNA, which shows the low risk of transfusion transmission in the region studied. However, the serologically assessed showed the detection of a properly positive sample for anti-ZIKV IgG (0.55%) and 4 samples with optical density (OD) values in the gray zone of the test. Due to the high rate of cross-reaction between the different flaviviruses all samples (including the positive) were assessed to confirmatory testing for anti-DENV IgG (Anti-Dengue Virus ELISA IgG, Euroimmun, Medizinische Labordiagnostika AG, Lübek, Germany). The positive sample for anti-ZIKV IgG was negative for anti-DENV IgG, confirming the positive result for anti-ZIKV IgG. However, 3 gray zone seroreactive samples showed very high title of anti-DENV IgG and one remained in the gray zone. Confirmatory analysis of this sample using in-house ELISA with anti-DENV IgG antibody adsorption revealed that it was negative for anti-DENV IgG. This indicates a 0.55% seroprevalence of ZIKV in the Santa Maria-RS region. Our results demonstrate that the transfusional risk of ZIKV in the South of the Country is relatively low, however, it cannot be underestimated and serological analyses of large numbers of samples are required to determine the exact seroprevalence of anti-ZIKV and anti- DENV IgG in blood donors in the region of Santa Maria.